Test dosing as an alternative treatment approach in urinary tract infection patient with Cefoperazone allergy - Komara, I. Made Adi Narendranatha; Suryana, Ketut (International Journal of Advances in Medicine, 2021)
Drug hypersensitivity reaction (DHR) is classified as adverse reaction which is based on immunologic mediated reaction. Antibiotics are the most frequently prescribed drugs given to patients to treat bacterial infections, but also cause adverse drug reactions due to hypersensitivity in patients. We present here a case of cefoperazone drug allergy in a 75 years old patient with urinary tract infection requiring the test dosing approach.